Quality of Service for the Delivery Guarantee Program (Jampersal) for the Implementation of Regional Regulations on Public Service Retribution in Banyumas Regency - Diah Arimbi; Retno Kumalasari (Universitas Katolik Soegijapranata Semarang, 2020)
Abstract: Maternal and perinatal health problems are national problems that need to be given top priority. The health status of a community is assessed through several indicators, including the Maternal Mortality Rate and the Infant Mortality Rate. To accelerate the achievement of the Millennium Development Goals (MDGs) in 2015, especially in reducing maternal and infant mortality rates, this year the Ministry of Health launched the Maternity Insurance (Jampersal) program. In reducing the Maternal Mortality Rate and Infant Mortality Rate (IMR), all sectors are required to cooperate. There are problems, including the existence of jampersal health service fees, midwives in Banyumas district have complained about the existing fees, in this case making delamatis as quality health service workers not matched with proper services. Jampersal's satisfaction is still a sign of whether Jampersal gives satisfaction to patients or even Jampersal officers themselves. This research aims to review the service quality of the Maternity Guarantee Program (Jampersal) as the Application of Local Regulations on Health Services in the Bayumas Regency. The research method is qualitative. The research subjects were private practice midwives and health centers in Banyumas Regency. As a triangulation is the Semarang City Health Office Maternity Insurance Manager and the coordinator of the IBI (Indonesian Midwives Association) midwife. Data collection was carried out through in-depth interviews. State output plays a role in health services for its people. Especially for the weak by the mandate of the 1945 Constitution Articles 28H and 34. The quality of service for the birth insurance program (Jampersal) as the application of regional regulations on health services, does not affect the quality of quality services for patient safety and their duties. The highest service satisfaction assessment is the assessment of the work aspect of a midwife who is in charge of serving and caring for patients as a noble job. Keywords: Quality, Jampersal, Regional Regulation Abstrak: Masalah kesehatan ibu dan perinatal merupakan masalah nasional yang perlu mendapatkan prioritas utama. Derajat kesehatan suatu masyarakat dinilai melalui beberapa indikator diantaranya dengan Angka Kematian Ibu dan Angka Kematian Bayi. Untuk mempercepat pencapaian Millenium Development Goals (MDGs) tahun 2015 khususnya menurunkan angka kematian ibu dan bayi, tahun ini Kementerian Kesehatan meluncurkan program Jaminan Persalinan (Jampersal). Dalam menurunkan Angka Kematian Ibu dan Angka Kematian Bayi (AKB) perlulah kerjasama semua sektor. Adanya permasalahan yang diantaranya adanya retribusi jasa pelayanan kesehatan jampersal,bidan di kabupaten Banyumas banyak mengeluhkan retribusi yang ada, dalam hal ini menjadikan delamatis sebagai tenaga kesehatan pelayanan berkualitas tidak diimbangi dengan jasa yang semestinya. Kepuasan Jampersal yang masih menjadi tanda atanya, apakah Jampersal memberikan kepuasan kepada pasien atau bahkan petugas Jampersalnya itu sendiri.Tujuan penelitian untuk meninjau kualitas layanan Program Jaminan Persalinan (Jampersal) Sebagai Penerapan Peraturan Daerah Tentang Jasa Pelayanan Kesehatan di Kabupaten Bayumas. Metode penelitian adalah kualitatif. Subjek penelitian adalah bidan praktek swasta dan di puskemas di wilayah Kabupaten Banyumas. Sebagai Triangulasi adalah Pengelola Jaminan Persalinan Dinas Kesehatan Kota Semarang dan koordinator bidan IBI (Ikatan Bidan Indonesia). Pengumpulan data dilakukan melalui wawancara mendalam. Hasil negara berperan dalam pelayanan kesehatan bagi rakyatnya. Terutama bagi kaum lemah sesuai amanat UUD 1945 Pasal 28H dan 34. Kualitas layanan program jaminan persalinan (Jampersal) sebagai penerapan peraturan daerah tentang jasa pelayanan kesehatan, tidak mempengaruhi kualitas pelayanan yang bermutu bagi keselamatan pasien dan tugasnya. Penilaian kepuasan pelayanan yang tertinggi yaitu penilaian aspek pekerjaaan seorang bidan yang bertugas melayani dan merawat pasien sebagai suatu pekerjaan yang mulia.Kata kunci: Kualitas, Jampersal, Pearaturan Daerah